DEVELOPMENT OF PUSKESMAS LOCATION SEARCH APPLICATIONS IN DKI JAKARTA USING HARVESINE METHOD - Difa Bagas Atmaja; Syaifudin; Teddy Siswanto (Intelmatics, 2023)
The development of this application aims to produce information from the raw data of health centers in the DKI Jakarta province in 2017 which are still in the form of datasets for later data sets to be processed into an information center where this application focuses on searching the location of the puskesmas. This application uses the harvesine formula as the method of searching for the nearest health center and the waterfaal model as its development method. Using Puskesmas spatial data in the form of latitude and longitude coordinates and non-spatial data in the form of names, addresses and so on are processed into useful information for the Indonesian people, especially those in the DKI Jakarta province to make it easier for people to access information on community health centers.